Análisis de generación distribuida en hogares y edificaciones - Chuqui Quinteros, Manuel Milton (2014)
This work presents a comprehensive overview of Distributed Generation, as well as various forms of convenient application to get the greatest benefit when implemented in homes and buildings. Besides a description of the various advantages and disadvantages of such generation is presented, together with a study of inclusion in our country, in order to generate an interest to invest in this field is still largely untapped. It was necessary to analyze the international together with national legislation, establishing some comparisons, to determine the benefits that could promote greater participation by private investment and consequently a subsequent implementation in distribution systems and residential, looking for the benefit of both the state as well as the investor. At the end of this paper the results of both a technical and economic analysis, which is a demonstrated technical feasibility and economic viability, the same as those described in the findings and leading to present relevant recommendations based on the results reported obtained.